Cold stored platelets in treatment of bleeding. (20th October 2017) - Apelseth, T. O.; Cap, A. P.; Spinella, P. C.; Hervig, T.; Strandenes, G.
Abstract : The success of whole blood transfusion in military operational settings has engaged a debate on reintroduction of cold‐stored whole blood in treatment of critical bleeding in civilian health care. The haemostatic function of platelets stored cold at 4°C has however been questioned. In this review, we discuss the effects of cold storage on platelets, whether stored in whole blood or as platelet concentrates. Cold storage of platelets was abandoned during the 1970s due to reduced circulation time. Haemostatic superiority of cold‐stored platelets was however suggested. In vitro studies show reduced risk of bacterial contamination and equal or superior haemostatic qualities in cold‐stored platelet concentrates when evaluated by metabolic measures and aggregation response. Data on cold‐stored platelet concentrates from thrombocytopenic patients and healthy volunteers indicate improved platelet aggregation and reduced bleeding. A randomized controlled trial in paediatric patients undergoing cardiac surgery, showed reduced blood loss and improved platelet aggregation responses after transfusion with whole blood stored cold for up to 48 h, and platelets stored cold within whole blood for up to 15 days provide similar post‐storage platelet viability as platelet concentrates or apheresis platelets stored for less than 3 days. Animal studies also suggest efficacy of cold‐stored platelets. A study investigating the effects of cold‐stored apheresis platelets in patients undergoing cardiothoracic is currently being performed in Bergen, Norway showing promising results. We conclude that in vitro and clinical studies indicate that cold‐stored platelets may be beneficial in treatment of critical bleeding.